China into the Hu-Wen era : policy initiatives and challenges / [Edited by] John Wong; Hongyi Lai - Hongyi, Laiedited
This volume is an updated survey and assessment of the recent policy initiatives of Hu Jintao and Wen Jiabao, which have come to be known as the Hu-Wen's New Deal. Individual chapters are written by scholars from different academic disciplines and backgrounds. These scholars hail from Singapore, the United States, Australia, Korea, Hong Kong, Taiwan and Mainland China. Topics cover the patterns and process of leadership succession, emerging political factions, social unrest, sources of economic growth, income disparities, social security reform, land use policy, banking reform, corporate gover.